EXISTENCE OF THE DISTINCTION PRINCIPLE AS A PROTECTION FOR THE VICTIMS OF ARMED CONFLICT; THE IMPLICATIONS ON RENEWAL OF THE NATIONAL LAW - Danial Danial (Faculty of Law, Universitas Jenderal Soedirman, 2015)
This study intent to analyze the existence of the distinction principle in international humanitarian law can provide effective protection against combatants and civilians in a modern armed conflict and contribute to the protection of victims of internal conflicts in Indonesia. It is very important to find the concept of the protection of victims of internal conflict in Indonesia. This research uses a normative, and the research also applies a descriptive-analytical approach to examine and analyze the research questions of the thesis. In doing so, this research uses a secondary data, these legal materials are subsequently analyzed using a qualitative juridical approach. The results showed that the existence of distinction principle at the level of concepts and implementations provide less effective protection against combatants and civilians in modern armed conflict. And the contribution of distinction principle to the protection of victims of internal conflicts in Indonesia is able to strengthen the concept of “sishankamrata” and national legislation. Keywords: armed conflict, distinction principle, protection of victim.